Prestasi Belajar Siswa dan Tingkat Pendidikan Orang Tua (Studi Korelasi Siswa Sekolah Dasar di Kota Jayapura) - Putra, Muhammad Irwan (Civiliza Publishing, Indonesia., 2024)
This article discusses the level of student education and student learning achievement in Abepura as well as the influence of parental education level on student learning achievement in elementary schools in the Jayapura city area. This study aims to investigate the extent of the relationship between student learning achievement at primary school level and parents' education level. This research method is quantitative. Data collection is carried out through initial observation activities on research objects, data collection in the form of distributing questionnaires to respondents, data analysis or reviewing data obtained from various sources, and drawing conclusions from the data that has been analyzed. The results of the research conducted by researchers are that the formal education level of parents is still relatively low, this can be seen from the data from respondents from parents and guardians whose educational background is less than a bachelor's degree, and the level of parental education greatly influences the students' learning achievement.